COVID-19 Pandemisinin Diş Hekimliği Hastaları Üzerine Etkisinin Path Analizi Kullanılarak Değerlendirilmesi - Figen Kaptan; Gözde Sarak; Güher Barut; Vahide Hazal Abat (Selcuk Dental Journal)
Background: During the pandemic, which continues all over the world and progresses in Turkey, it is a priority to understand patients’ knowledge level concerning this contagious disease and understand patients’ attitude during their dental problems and also level of anxiety that could cause misbehavior. This study aims to synthesize and analyze existing evidence on the level of knowledge, awareness as to COVID-19, anxiety, and depression of Turkish dental patients. Methods: This survey consisting of 32 questions included demographic information, knowledge about COVID-19, the awareness of the importance of COVID-19 in dental treatments, and the Hospital Anxiety and Depression Scale. The survey was performed from September 20, 2021 to January 20, 2021 on a voluntary basis, and 837 participants responded all the questions in the survey. Path analysis was used to evaluate the relations of variables. Chi-Square tests were used to evaluate qualitative data. The statistical significance level was set at p < 0.05. Results: COVID-19 knowledge level was determined as 92.85 ± 11.47 (100) (min ± SD). 97.3 % of the patients (n=814) reported that they wanted to reach their doctor in case of emergency toothache. 4.2 % (n= 35) reported that they did not know what to do for emergency tooth pain. Conclusion: It has been clearly demonstrated that just knowing about COVID-19 does not reduce anxiety and depression levels. It has been revealed that anxiety and depression levels are lower in patients with high awareness. Keywords: anxiety, COVID-19, dentistry, depression, health surveys